2012
DOI: 10.1126/science.1219861
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Detectable Arsenate in DNA from Arsenate-Grown GFAJ-1 Cells

Abstract: A strain of Halomonas bacteria, GFAJ-1, has been reported to be able to use arsenate as a nutrient when phosphate is limiting, and to specifically incorporate arsenic into its DNA in place of phosphorus. However, we have found that arsenate does not contribute to growth of GFAJ-1 when phosphate is limiting and that DNA purified from cells grown with limiting phosphate and abundant arsenate does not exhibit the spontaneous hydrolysis expected of arsenate ester bonds. Furthermore, mass spectrometry showed that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 11 publications
(34 reference statements)
0
80
0
1
Order By: Relevance
“…The scientific response to the apparent finding of bacteria (GFAJ‐1) living in an arsenic‐rich, phosphate‐free environment,6 and suggesting the existence of arseno‐DNA, was comprehensive: chemists noted that the rates of hydrolysis50 and reduction51 of arsenate esters would predict a prohibitively low stability for arseno‐DNA; furthermore, biologists showed that trace levels of phosphate were present and sufficient for bacteria,7 and found no detectable arsenic in their DNA 52. It transpired that the bacteria are able to tolerate high arsenate/low phosphate environments because they can be extremely selective in their uptake of the two: a phosphate‐binding protein (PBP) up‐regulated by GFAJ‐1 in phosphate‐poor conditions has a 4500‐fold preference for phosphate over arsenate.…”
Section: Macromolecular Recognition Of Anions In Watermentioning
confidence: 99%
“…The scientific response to the apparent finding of bacteria (GFAJ‐1) living in an arsenic‐rich, phosphate‐free environment,6 and suggesting the existence of arseno‐DNA, was comprehensive: chemists noted that the rates of hydrolysis50 and reduction51 of arsenate esters would predict a prohibitively low stability for arseno‐DNA; furthermore, biologists showed that trace levels of phosphate were present and sufficient for bacteria,7 and found no detectable arsenic in their DNA 52. It transpired that the bacteria are able to tolerate high arsenate/low phosphate environments because they can be extremely selective in their uptake of the two: a phosphate‐binding protein (PBP) up‐regulated by GFAJ‐1 in phosphate‐poor conditions has a 4500‐fold preference for phosphate over arsenate.…”
Section: Macromolecular Recognition Of Anions In Watermentioning
confidence: 99%
“…Unsuccessful attempts to replicate findings in genetics (1), pharmacology (2), oncology (3), biology (4), and economics (5) have given credence to previous speculation that most published research findings are false (6). Indeed, since the launch of the clinicaltrials.gov registry in 2000, which forced researchers to preregister their methods and outcome measures, the percentage of large heart-disease clinical trials reporting significant positive results plummeted from 57% to a mere 8% (7).…”
mentioning
confidence: 99%
“…In July 2012, Science published an article in which Redfield and collaborators replicated the original arsenic study (10). Blogging during the research process was no obstacle.…”
mentioning
confidence: 86%